Protein intake recommendation for stunted children: an update review. - Fikri, Al Mukhlas; Astuti, Widya; Nurhidayati, Vieta Annisa; Prameswari, Fajria Saliha Puspita; Ismail, Nazrul Hadi (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: Childhood stunting remains a pervasive global health issue affecting millions of children, with significant repercussions on their physical and cognitive development. Objective: This study aimed to collect information on dietary guidelines and protein recommendation specifically designed for stunted children. Methods: A systematic review was performed using several databases, including Pubmed, Scopus, and Google Scholar. A literature search was conducted to collect studies on dietary guidelines (keywords: Dietary recommendation OR Dietary Guidelines AND Stunting OR Stunted OR Retarded Growth) and protein recommendation (keywords: protein AND catch-up growth AND stunting AND children OR infant) for stunted children. This review also included a narrative review for additional information. Results: A total of 12 and 9 related articles were included in this systematic review on dietary guidelines and protein intake, respectively. This systematic review shows that protein intake stands out as a critical determinant in stunting, with low intake associated with growth faltering. However, guidelines specifically tailored to manage stunting remain scarce. Current evidence suggests protein’s beneficial role in supporting linear growth, but excessive intake may contribute to obesity risk, highlighting the need for balanced recommendations. Conclusion: This review synthesizes existing knowledge on protein’s role in stunting management, emphasizing the importance of appropriate protein intake in promoting optimal growth while mitigating associated risks.